Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-588
|View full text |Cite
|
Sign up to set email alerts
|

Role of Blade Passage Flow Structures in Axial Compressor Rotating Stall Inception

Abstract: The influence of three-dimensional flow structures within a compressor blade passage has been examined computationally to determine their role in rotating stall inception. The computations displayed a short length-scale (or spike) type of stall inception similar to that seen in experiments; to the authors’ knowledge this is the first time such a feature has been simulated. A central feature observed during the rotating stall inception was the tip clearance vortex moving forward of the blade row leading edge. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 9 publications
4
72
1
Order By: Relevance
“…10(e, f). The localized disturbance is caused by interaction of the tip leakage flow and the main flow in a subsonic axial compressor, as Hoying et al 20) reported, when the front line of the tip leakage flow propagates forward of the leading edge plane. Hah et al 23) showed that interaction between the tip leakage flow and the passage shock causes a local disturbance in a transonic axial compressor.…”
Section: Unsteady Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…10(e, f). The localized disturbance is caused by interaction of the tip leakage flow and the main flow in a subsonic axial compressor, as Hoying et al 20) reported, when the front line of the tip leakage flow propagates forward of the leading edge plane. Hah et al 23) showed that interaction between the tip leakage flow and the passage shock causes a local disturbance in a transonic axial compressor.…”
Section: Unsteady Flowmentioning
confidence: 99%
“…In recent years, many numerical studies on the rotating stall have been published. [17][18][19][20][21][22][23][24] Hoying et al 20) established a relationship between stall inception and trajectory of the center of the tip leakage flow, hypothesizing that a disturbance is initiated from the vortex motion of the tip leakage flow. Niazi 24) conducted both simple numerical simulations and numerical tests of control techniques for the rotating stall.…”
Section: Introductionmentioning
confidence: 99%
“…A disturbance near the casing might be caused by the interaction of the tip leakage flow and the main flow in a subsonic axial compressor, as Hoying et al 9) have reported, when the front line of the tip leakage flows propagates forward of the leading edge plane. However, the first localized disturbance in this study originated before the front line of the tip leakage flows reached the leading edge plane, meaning there is another mechanism triggering a disturbance.…”
Section: Unsteady Flowmentioning
confidence: 99%
“…In recent years, many numerical studies on rotating stall have been published. [8][9][10][11][12] These numerical results showed the stall inception process in detail and gave an intuitive understanding about the characteristics of rotating stall. Especially, Vahdati et al 11) recently analyzed the effects of rotating stall on aero-engine core compressor vibration and Vo et al 12) established two criteria for spike-type rotating stall, namely tip clearance back flow at the trailing edge and leading-edge tip leakage flow spillage below the blade tip.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have been done on rotating stall and surge for compressors, axial compressors particularly. For example, the process leading to the formation of finite amplitude rotating stall cells has been extensively studied experimentally and numerically [1][2][3]. It is said that two types of rotating stall inception occur in axial compressors.…”
Section: Introductionmentioning
confidence: 99%